How is the Effect of Health Services on Toddler Diarrhea?: Ecological Analysis in Indonesia - Yuli Puspita Devi; Milla Herdayati; Muthmainnah; Mahdiyyah Husna Nihar; Imas Elva Khoiriyah; Az-Zahra Helmi Putri Rahayu (Institute of Medico-legal Publications Pvt Ltd, 2022)
Background: About 4 billion cases of toddler diarrhea occur worldwide each year. As many as 70% of toddler deaths in the world were caused by diarrheal infections. This study was intended to analyze the relationship of health services factors on the prevalence of diarrhea of infants in Indonesia.Methods: Ecological analysis was conducted using secondary data from the Ministry of Health of the Republic of Indonesia report in 2018. All provinces were taken as samples. Apart from prevalence of children under five with diarrhea, 4 other variables analyzed as independent variables were, the availability of health workers, the coverage of diarrhea services and the coverage of oralit services to the patients, the coverage of zinc services to the patients, and the poverty factors in each provinces. Data were analyzed using cross-tabulation and spearman test.Results: The results show from 34 provinces, the highest prevalence of toddlers is in the Papua Province. The results showed that the higher the percentage of poor people in the province, the higher the prevalence of diarrhea in toddlers (r=0.363). While the low availability of health resources, coverage of oralit use, and coverage of zinc use in patients were mostly occurring in provinces that had a high prevalence of toddler diarrhea. This means that there was an inverse relationship between the availability of health resources (r=-0.430), the coverage of oralit use (r=-0.149) and the coverage of zinc use in patients (r=-0.013) with the prevalence of diarrhea in toddlers.Conclusion: It was concluded that according to bivariate analysis on the prevalence of diarrhea of toddlers showed that increasing availability of health resources in the provinces can help to reduce the prevalence of toddlers by assuming other variables remain.